The Impact of the Strategy of “Find the False Statement” on the Achievement of the First Year students in the Intermediate School in the Subject of the Holy Quran and Islamic Education and How it Participate in the Development of their Social Values - Al- Jubouri, Falah Saleh Hussein; Hamid Khader Jubouri, Najla Abdul Jalil (Journal of Tikrit University for Humanities, 2020)
The current research aims to identify the impact of the strategy of finding error in the achievement of intermediate school students in the Holy Qur’an and Islamic education and developing their social values. In order to verify this objective, the researchers formulated the following hypotheses: 1- There is no statistically significant difference at the level of significance (0.05) between the average scores of female students in the experimental group and the average scores of female students in the control group in the achievement of the Holy Quran and Islamic education. In order to verify this research objective, the researcher formulated the following hypotheses: 2- There is no statistically significant difference at the level (0.05) between the average difference between the degrees of students of the experimental group, and the average difference between the degrees of students of the control group to develop their social values in the post-test. 3- There is no statistically significant difference at the level of significance (0.05) between the average scores of students of the experimental group in the pre and post-tests of social values. The researchers balanced the two research groups according to a number of related variables. In order to conduct the experiment, the researchers prepared an achievement test with a number of (30) items, while the social values scale included (30) items.